2014
DOI: 10.1093/jac/dku112
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in the discontinuation of first-line antiretroviral therapy

Abstract: Discontinuation rates of first-line therapy have decreased over time, but are still quite high even for the latest drug combinations. In the most recent era, younger women on a PI regimen and those not achieving optimal adherence had the highest risk of discontinuing first-line antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 34 publications
6
28
0
Order By: Relevance
“…The discontinuation rate of third agent and NRTI backbone of 28 (95% CI 26–31) and 15 (95% CI 14–17) per hundred person-years respectively are comparable to those seen in other high-income settings: in an Italian cohort of 4052 patients starting ART between 2008 and 2014, discontinuation rates at 1,2 and 3 years were 26%,40% and 49%, respectively 8 . These are similar to data from British Columbia, Canada, where the ART discontinuation rates of 2107 patients who initiated therapy between 2006 and 2010 were 36%, 47% and 53% at 1, 2 and 3 years, 9 and Switzerland, where the rate of discontinuation of initial treatment in 1318 treatment-naïve patients was 42 per 100 person-years (95% CI 38–46) 10 . Older data from the UK are available from the UK CHIC cohort 11 ; of 4583 patients initiating ART between 2000 and 2010, 15–19% discontinued therapy after one year (with exact proportion dependent on CD4 count); however, when patients who were also enrolled in the SPARTAC study of ART at seroconversion were excluded, the remaining 1746 patients had one-year discontinuation rates of 28–31%, highlighting the difference between clinical trial and real-world populations.…”
Section: Discussionsupporting
confidence: 81%
“…The discontinuation rate of third agent and NRTI backbone of 28 (95% CI 26–31) and 15 (95% CI 14–17) per hundred person-years respectively are comparable to those seen in other high-income settings: in an Italian cohort of 4052 patients starting ART between 2008 and 2014, discontinuation rates at 1,2 and 3 years were 26%,40% and 49%, respectively 8 . These are similar to data from British Columbia, Canada, where the ART discontinuation rates of 2107 patients who initiated therapy between 2006 and 2010 were 36%, 47% and 53% at 1, 2 and 3 years, 9 and Switzerland, where the rate of discontinuation of initial treatment in 1318 treatment-naïve patients was 42 per 100 person-years (95% CI 38–46) 10 . Older data from the UK are available from the UK CHIC cohort 11 ; of 4583 patients initiating ART between 2000 and 2010, 15–19% discontinued therapy after one year (with exact proportion dependent on CD4 count); however, when patients who were also enrolled in the SPARTAC study of ART at seroconversion were excluded, the remaining 1746 patients had one-year discontinuation rates of 28–31%, highlighting the difference between clinical trial and real-world populations.…”
Section: Discussionsupporting
confidence: 81%
“…Kwobah et al [21] identified that non adherence was associated with almost three times the odds of treatment failure and Gonzalez-Serna et al [22] found that an adherence level greater than or equal to 95% independently reduced treatment discontinuation by 61%. Ickovics et al [14] have reported that HIV/AIDS patients whose degree of adherence was less than 95% were 3-5 times more likely to have treatment failure compared to those with adherence levels of 95% or higher and treatment failure is one of the most common reasons to switch therapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Many HIV studies [21,22] so far have looked at treatment failure and discontinuation of ART from the perspective of temporal trends or taxonomy of possible determinants. The present study aims to elucidate a possible association between insufficient adherence to ART and treatment change among HIV/AIDS patients at the Korle-Bu Teaching Hospital in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the known clinical benefits of long-term medication use for many chronic conditions, including HIV infection, a large proportion of patients who appropriately initiate medications do not persist with medication taking or experience gaps in treatment [3]. In previous studies, half of HIV patients using antiretroviral therapy (ART) had discontinued treatments by 2 years, and half of the patients with hypertension had discontinued treatments by 3 years [47]. Persistence with medications is especially challenging for asymptomatic chronic conditions for which treatment side effects and complications are typically experienced immediately, but for which health benefits are delayed, often for years [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no population-based estimates of the rates of persistence with ART in the United States. How these rates have changed over the time period during which newer ART regimens became available, demographics of the HIV population changed, and many HIV clinics implemented adherence programs is also unknown [4, 12]. …”
Section: Introductionmentioning
confidence: 99%